Epidemic Trends in High Tuberculosis Burden Countries During the Last Three Decades and Feasibility of Achieving the Global Targets at the Country Level - Ding, Cheng; Hu, Ming; Shangguan, Yanwan; Guo, Wanru; Wang, Shuting; Feng, Xuewen; Zhang, Zunjing; Zhang, Ying; Xu, Kaijin (Frontiers in Medicine, 2022)
Objective: To estimate the epidemic trends in 30 high burden countries (HBCs) of tuberculosis (TB) over the past 30 years at the country level, which is crucial to tracking the status of disease control, especially at the country level. Methods: Annual case data on incidence and mortality of tuberculosis in these 30 HBCs were extracted from the Global Burden of Disease database. The average annual percent change (AAPC) was used to evaluate the trends of incidence and mortality. The trajectory analysis was used to identify different trends among the subgroup countries. The predicted incidence and mortality rates in 2025, 2030 and 2035 were also calculated Results: The incidence and mortality decreased in most of the HBCs. The AAPCs of incidence ranged between -4.0% (Indonesia) and -0.2% (DR Congo) (all P<0.05). The incidence trends in Lesotho (AAPC: 0%, 95% CI: -0.4, 0.3, P=0.8) and South Africa (AAPC: -0.2%, 95% CI: -0.5, 0, P=0.1) were stable, and increased in Kenya with AAPC of 0.1% (95% CI: 0.1, 0.2, P<0.05). The AAPCs for mortality ranged between -5.8% (Ethiopia) and -0.6% (Central African Republic) (all P<0.05). The mortality trends in DPR Korea (AAPC: 0.1%, 95% CI: -0.3, 0.4, P=0.6) and Russian Federation (AAPC: -0.5%, 95% CI: -1.9, 0.9, P=0.5) were stable, and increased in Lesotho and Zimbabwe with AAPC of 1.3% (95% CI: 1.1, 1.4, P<0.05) and 1.6% (95% CI: 1.0, 2.2, P<0.05), respectively. Trajectory analysis showed that Central African Republic, Lesotho, Cambodia, Namibia and South Africa had higher incidences, and Central African Republic had the higher mortality. Brazil and China had relatively lower rates of incidence and mortality. Predictions showed that reduction rates of incidence and mortality could hardly be reached compared to those set for the global targets for the majority HBCs. Conclusions: Disease burden of TB reduced among the majority HBCs over the last three decades. According to the current control levels, achieving the ambitious global targets at national level for these 30 HBCs is challenging.